Effects of low-dose combined drospirenone–ethinylestradiol on perimenstrual symptoms experienced by women with endometriosis. Issue 2 (November 2016) - Tanaka, Yukiko; Mori, Taisuke; Ito, Fumitake; Koshiba, Akemi; Kusuki, Izumi; Kitawaki, Jo
Abstract: Objective: To determine the effectiveness of a 24/4-day regimen of a low-dose combination drospirenone–ethinylestradiol oral contraceptive in alleviating perimenstrual symptoms among Japanese women with endometriosis. Methods: The present prospective, non-randomized study enrolled women diagnosed with endometriosis radiographically or surgically at the Kyoto Prefectural University of Medicine hospital, Japan, between December 1, 2010 and August 31, 2013. Patients received treatment with oral drospirenone–ethinylestradiol for six treatment cycles. Dysmenorrhea, chronic pelvic pain, and dyspareunia severity were assessed using visual analog scale scores after three and six treatment cycles, and changes in perimenstrual symptoms were assessed using the menstrual distress questionnaire (MDQ) scores. Results: In total, 46 patients were recruited for the study. Dysmenorrhea, chronic pelvic pain, and dyspareunia were all significantly reduced after both three and six treatment cycles in comparison with baseline ( P  < 0.001 for all comparisons). After six treatment cycles, significant reductions were observed for all menstrual MDQ measures and for the premenstrual water retention and negative-effect MDQ measures (all P  < 0.05). Conclusions: Combination drospirenone–ethinylestradiol was effective in the treatment of dysmenorrhea, chronic pelvic pain, dyspareunia, and somatic/psychological symptoms in Japanese women with endometriosis.